2015
DOI: 10.1089/vbz.2015.1806
|View full text |Cite
|
Sign up to set email alerts
|

Serological Evidence of Infection byLeishmania (Leishmania) infantum(Synonym:Leishmania (Leishmania) chagasi) in Free-Ranging Wild Mammals in a Nonendemic Region of the State of São Paulo, Brazil

Abstract: Concerns about the interface between wildlife, domestic animals, and humans in the transmission of visceral leishmaniasis (VL) have been growing due to natural or anthropogenic environmental changes. In this context, investigations of the infection in wild mammals are important to assess their exposure to the vector and the parasite. A study of anti-Leishmania (Leishmania) infantum antibodies was carried out using the direct agglutination test (DAT) on 528 free-ranging wild mammals of 38 species from the regio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 37 publications
0
11
1
1
Order By: Relevance
“…Regarding leptospirosis, our results contradict these thoughts. Likewise, in preliminary studies, we found low prevalence of toxoplasmosis (Fornazari et al, 2011), leishmaniasis (Paiz et al, 2015) and brucellosis (Antunes et al, 2010). Thus, contrary to our initial thoughts, so far there is no evidence that opossums are important carriers of zoonoses in Botucatu.…”
Section: Discussioncontrasting
confidence: 90%
“…Regarding leptospirosis, our results contradict these thoughts. Likewise, in preliminary studies, we found low prevalence of toxoplasmosis (Fornazari et al, 2011), leishmaniasis (Paiz et al, 2015) and brucellosis (Antunes et al, 2010). Thus, contrary to our initial thoughts, so far there is no evidence that opossums are important carriers of zoonoses in Botucatu.…”
Section: Discussioncontrasting
confidence: 90%
“…Several studies investigated free-ranging carnivores by serology using a direct agglutination test (DAT), and positive values were found in tayras (Eira barbara), lesser grison (Galictis cuja) and coatis (Nasua nasua) in Brazil at high serum dilutions (≥1:1280) [92]. In carnivores kept in captivity, serology was also employed to demonstrate the presence of antibodies against the parasites in ocelots (Leopardus pardalis), hoary foxes (Lycalopex-Pseudalopex vetulus), jaguars (Panthera onca), Siberian tigers (Panthera tigris altaica), African lions (Panthera leo) and cougars (Puma concolor) (Supplementary Materials File S4) [84,90,93,94].…”
Section: Infantum In the Americasmentioning
confidence: 99%
“…Lagomorphs were scarcely reported as exposed to L. infantum in the Americas, with one European hare (Lepus europaeus) found positive in Brazil by DAT and with a low antibody titre (1:320) [92].…”
Section: Infantum In the Americasmentioning
confidence: 99%
See 2 more Smart Citations